Efecto de tres abonaduras orgánicas en el cultivo de apio (apium graveolens) en la zona de la Libertad Cantón Espejo, Provincia del Carchi - Torres Narváez, Cástulo Lidio (2012)
This researchaddressed theagronomic performanceof the cropofceleryversusorganicfertilization, in order toevaluate the agronomic performanceof the cropcelerywiththe applicationof organic, treatment andidentifythe most effective doseof each ofthefertilizersappliedandeconomicallyanalyzethe treatments. We useda randomized complete blockdesign(RCBD) with7 treatmentsand 3 replications, witha total of 21experimental units.The total areaof the experiment was322.4m2, each experimental plotwas 7.2m2with ausable areaof151.20m2. Variableswere evaluated: plant height, stem diameter, number of leaves per plant, rootfresh weight, root sizeandgoodplant vigor, yield per plant. All variableswere subjectedto analysisof varianceto determinethe statistical differencebetweentreatment means, we used the Tukey test at5%significance.